Biomarkers in diagnosis and treatment of ovarian cancer - Rogulski, Lech; Olejek, Anita (Menopause Review/Przegląd Menopauzalny, 2008)
Diagnosis and treatment of ovarian cancer are still a challenge for modern gynaecology. Lack of sufficiently specific symptoms and unclear molecular pathogenesis make early detection very problematic. Ovarian cancer is mostly diagnosed in clinical stage III and IV when optimal surgery is often impossible and medical treatment is less effective. Management of high-risk patients is also an unsolved issue. Employing biomarkers may lead to development of a successful screening strategy thus prolonging patient survival. CA-125 antigen has been used for many years as an ovarian cancer marker but it lacks both sensitivity and specificity to augment early stage detection. Its clinical usefulness is limited to treatment monitoring and differentiating between malignant and benign adnexal masses. Proteomic methods and transcription profiling are molecular biological techniques that were used to identify and thoroughly examine potential markers of ovarian malignancies. The most promising include HE4, mesothelin, inhibin, activin and tissue kallikreins. Attaining high sensitivity and specificity only seems possible when single markers are combined in diagnostic panels by means of advanced statistical methods. Another important field of research is determination of cancer cells’ drug resistance which would allow guided therapy. The scope of the following work is a concise presentation of the current state of knowledge on ovarian cancer biomarkers.